(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The re-insurance of the same important role in the development programs and activities that reinsurance companies and their level of development and the mechanisms of action and the laws that govern the relationship between the re-insurance companies and direct companies reflect the cultural level and degree of progress of any country. As well as natural that philosophy Reinsurance reflect the extent of the security risks that are located, whether f0 money or to persons or property in accordance with the contractual terms of parallel . Given the importance of re-insurance sector and the need to develop the level of his performance came this research to identify the nature of the activity reinsurance companies. So came the goal of research in the study of the reality of reinsurance and the search for ways to help in activating the role of insurance and to minimize the negative effects of the disaster was search has included a review of previous studies and research that dealt with reinsurance risks catastrophic were also reviewed in the entrance and in detail (to re-secure the dangers catastrophic) in terms of importance and the concept of evolution as well as the nature of disasters and their causes and effects .